Indirect sexual selection drives rapid sperm protein evolution in abalone - Wilburn, Damien Beau; Tuttle, Lisa M; Klevit, Rachel E; Swanson, Willie J (eLife, 2019)
Sexual selection can explain the rapid evolution of fertilization proteins, yet sperm proteins evolve rapidly even if not directly involved in fertilization. In the marine mollusk abalone, sperm secrete enormous quantities of two rapidly evolving proteins, lysin and sp18, that are stored at nearly molar concentrations. We demonstrate that this extraordinary packaging is achieved by associating into Fuzzy Interacting Transient Zwitterion (FITZ) complexes upon binding the intrinsically disordered FITZ Anionic Partner (FITZAP). FITZ complexes form at intracellular ionic strengths and, upon exocytosis into seawater, lysin and sp18 are dispersed to drive fertilization. NMR analyses revealed that lysin uses a common molecular interface to bind both FITZAP and its egg receptor VERL. As sexual selection alters the lysin-VERL interface, FITZAP coevolves rapidly to maintain lysin binding. FITZAP-lysin interactions exhibit a similar species-specificity as lysin-VERL interactions. Thus, tethered molecular arms races driven by sexual selection can generally explain rapid sperm protein evolution.
Keywords: sexual selection; NMR spectroscopy; fertilization; abalone; rapid evolution